Potential change of chestnut (Castanea sativa Mill.) distribution areas in Kastamonu due to global climate change - Nihat ERTURK; Burak ARICAK (GSC Online Press, 2024)
Climate change, which is effective on a global scale, threatens almost all living things and ecosystems directly or indirectly. Forests are among the ecosystems that are predicted to be most affected by climate change. In this study, it was aimed to determine the current status of chestnut distribution areas in Kastamonu Forestry Regional Directorate, which is the Forestry Regional Directorate with the highest production in Türkiye, and the change in suitable distribution areas due to global climate change. In the study, in addition to the current suitable distribution areas of chestnut distribution areas and the current distribution area, the suitable distribution areas in 2040, 2070 and 2100 according to SSP 126, SSP 370 and SSP 585 scenarios were determined. The results of the study show that there will be a significant decrease in the suitable distribution areas of chestnut populations in Kastamonu due to the effects of climate change. Therefore, in order to prevent individual, population and species losses in the future, it is recommended to make necessary arrangements in forest management plans by taking the results of the study into consideration.
Keywords: Kastamonu; Global climate change; Castanea sativa; SSP scenarios; Habitat distribution